2016
DOI: 10.1681/asn.2015020191
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of X-Box Binding Protein-1 during Endoplasmic Reticulum Stress in Podocytes

Abstract: Podocytes are terminally differentiated epithelial cells that reside along the glomerular filtration barrier. Evidence suggests that after podocyte injury, endoplasmic reticulum stress response is activated, but the molecular mechanisms involved are incompletely defined. In a mouse model, we confirmed that podocyte injury induces endoplasmic reticulum stress response and upregulated unfolded protein response pathways, which have been shown to mitigate damage by preventing the accumulation of misfolded proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 42 publications
3
40
0
Order By: Relevance
“…described (75). The number of foot processes was divided by the total length of glomerular basement membrane regions in each electron microscopic image (76).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…described (75). The number of foot processes was divided by the total length of glomerular basement membrane regions in each electron microscopic image (76).…”
Section: Discussionmentioning
confidence: 99%
“…Images were taken by an Andor CSU-WDi spinning disc confocal microscope equipped with a Nikon Ti-E CFI Plan Apochromat Lambda ×60 oil immersion objective for immunofluorescence analysis, and images were processed using NIH ImageJ software (version 1.51H) or Adobe Photoshop CS 2014. For quantification of podocyte number, WT1-positive nuclei were counted in each glomeruli (77). For quantification of changes in actin cytoarchitecture of primary podocytes, podocytes stained with phalloidin were Figure 11.…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be a unique feature of collecting ducts because we had previously found that inactivating Sec63 in podocytes resulted in activation of at least the Ire1a-Xbp1 branch of UPR, which served as a compensatory mechanism to prevent podocyte dysfunction and loss. 25 Similarly, inactivation of Sec63 using Cdh16(Ksp)-Cre, which targets mTAL, DCT, and the collecting duct, resulted in activation of the Ire1a-Xbp1 pathway detectable in whole kidney lysates. Concomitant inactivation of Xbp1 resulted in worsening kidney cyst formation, corroborating the adaptive value of UPR activation in this model as well.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of Sec63, activation of Ire1a-Xbp1 and its transcriptional targets has an adaptive role in supporting maturation of polycystin-1 and, by inference, other Sec63 client proteins. 18,25,26 In this study, we set out to examine the effects of collecting tubule deletion of Sec63 and the Ire1a-Xbp1 pathway on kidney homeostasis and function. Surprisingly, we found that Sec63 inactivation in collecting ducts did not result in activation of the Ire1a-Xbp1 pathway or a discernible phenotype, but that concomitant inactivation of Ire1a or Xbp1 along with Sec63 caused a severe, progressive inflammatory and fibrotic response leading to kidney dysfunction.…”
mentioning
confidence: 99%
“…RhoGDI signaling may provide targets for HER2-positive breast cancer therapy. X-box binding protein 1 (XBP1) is the main regulator of endoplasmic reticulum stress (ERS) with basic lucien zipper structure [41] [42] . A large number of studies have shown that XBP1 is highly expressed in a variety of malignant tumor cells, and can promote the hypoxic survival of tumor cells and induce tumor metastasis and drug resistance [43] .…”
Section: Discussionmentioning
confidence: 99%